Public discourses of alternative protein foods in Facebook public pages’ posts, 2014–2024 - Weiyu Zhang; Bingyan Wang; Jingyi Xie; Lai Peng Leong; Tai Wei David Leong; Max Jing Rui Tham; Wee Han Ang (PLoS ONE, 2025)
“Alternative protein” (AP) refers to protein sources that are different from conventional animal-based proteins. This category encompasses a variety of highly processed plant-based proteins, cultured or cell-based meat, and is primarily driven by factors like sustainability, health, ethical concerns about animal welfare, and the need to feed a growing global population. The aim of this study is to map and understand public discourses around AP foods through social monitoring, in particular, computational analyses of social media big data. Through analyzing the topics and sentiments of Facebook public pages’ English content in the decade of 2014–2024, we found that (1) public attention on plant-based AP foods dropped since 2021, while attention on cell-based AP foods showed an uneven growth; (2) public sentiments towards plant-based AP foods were consistently positive, while sentiments towards cell-based AP foods were clearly more mixed; (3) discussion topics under plant-based AP foods were more practical and diverse than topics under cell-based AP foods; (4) the leading actors talking about AP foods were enterprises & industry, media, and organizations. Overall, plant-based AP foods have generated a more established and diverse public discourse, while cell-based AP foods are still emerging in public conversations and continue to face greater barriers to widespread understanding and acceptance.